Gastric Cancer An Update - Orita, Hajime; Maekawa, Hiroshi; Gibson, Michael (IntechOpen, 2019)
This book, Gastric Cancer - An Update, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of gastric cancer. The book is comprised of single chapters authored by various researchers and it is edited by experts active in this field of study. All chapters are complete in itself but united under a common research topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on gastric cancer, and opening new possible research paths for further novel developments.